Recoveries in the Middle East, North Africa, and Pakistan : Have Macroeconomic Policies Been Effective? - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2010)
This paper identifies and documents the properties of output gap recessions and recoveries in the Middle East, North Africa, and Pakistan (MENAP) during the 1980 to 2008 period. It goes on to investigate the key determinants of the recoveries. The duration of MENAP countries' recessions and recoveries has increased from the 1990s to the 2000s. MENAP hydrocarbon exporting countries' recessions were on average more pronounced in the 2000s, and hydrocarbon importing countries' recessions milder. Fiscal policy is found to have played a key role during the recoveries to potential output, although with weaker effects for MENAP countries that are more open to trade. Monetary policy is found to have been less effective. This is likely to be related to the fact that many of the MENAP countries have fixed exchange rate regimes and hence have limited room for active monetary policy.